An aptasensor for the detection of Pb2+ based on photoinduced electron transfer between a G‐quadruplex–hemin complex and a fluorophore. (29th September 2021) - Wang, Ya; Ye, Tai; Yuan, Min; Cao, Hui; Yu, Jingsong; Yin, Fengqin; Wu, Xiuxiu; Hao, Liling; Xu, Fei
Abstract: Due to the threat to health of heavy metal contamination, simple and rapid detection methods for heavy metals are an urgent needed in environment protection and food safety. In this work, we have developed a fluorescent aptasensor for the 'turn‐off' model detection of Pb 2+ . The key feature of the aptasensor is that the dye‐labelled nucleic acid strand can be folded into a G‐quadruplex structure in the presence of Pb 2+ . This conformational change induces photoinduced electron transfer (PET) between a G‐quadruplex–hemin complex and 6‐carboxyrhodamine X (ROX), which results in fluorescence quenching of ROX. We systematically investigated the interaction mechanism between Pb 2+ and the aptasensor and the effects of several environmental parameters were also studied. Under the optimum conditions, the proposed method exhibited a good liner relationship between the concentration of Pb 2+ and fluorescence quenching efficiency in the range 25–500 nM and the limit of detection was 1.02 nM. In addition, this method also manifested good performance in spiked lettuce samples with satisfactory recoveries of 87.10–109.6%. This target‐induced PET platform can be further expanded to other heavy metal analysis. Abstract : We have constructed an aptasensor for the detection of Pb 2+ based on photoinduced electron transfer. The G‐rich sequence, AGRO 100, folded into G‐quadruplex upon adding Pb 2+, where embedding hemin to form G‐quadruplex‐hemin complex as electron acceptor. In presence of Pb 2+, the fluorescent dye and G‐quadruplex‐hemin complex are in proximity that resulting in fluorescence quenching.